Stock-Flow Model for Forecasting Labor Supply - Sing, Michael; Love, Peter; Tam, C. (University of Johannesburg, 2012)
Forecasting the supply of labor in the construction industry is pivotal to long-te1m economic growth. A labor supply model using a stock-flow approach was developed in this research for use in the construction industry. The model was tested using Hong Kong census statistics and data derived from interviews with 3,000 randomly selected construction workers. The findings were determined using a stock-flow model, which enabled the determination of future aging distribution trends and workforce supply for specific trade types. The developed stock-flow model can be effectively used in countries in which registration schemes for construction workers are in use.